Types of dryers and their effect on the pistachio nuts quality - A Review. - Karim, Roselina; Chin, Nyuk Ling; Mohd Ghazali, Hasanah; Shakerardekani, Ahmad (2011)
This review discusses the performance of existing dryers for pistachio drying process, which is available in the literature. It encompasses sun drying, solar dryer, bin dryer, vertical continuous dryer, funnel cylindrical dryer, vertical cylindrical dryer, continuous mobile and steady tray dryer, drum dryer and continuous belt conveyor dryer. The split nut and shell appearance of pistachio nuts are significantly influenced by the drying methods. The types of dryer used for drying pistachio nuts are critical to the final quality of the product. Although sun drying has a good effect on the final product quality, the negative climatic and environmental conditions must be considered. A combination of bin dryer and sun drying or combination of bin dryer and solar dryer, are recommended as effective drying techniques to prevent adverse quality effect on pistachio nut.